2001
DOI: 10.1177/00027640121958276
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Format and Questions on Candidates' Strategic Argument Choices in the 2000 Presidential Debates

Abstract: Building on past content analyses of presidential debates to determine how format affects the levels of clash and candidates' strategies, this study answers three questions about the 2000 presidential debates: (a) Do candidates differ in their use of clash and nonclash argument strategies? (b) Does format affect candidates' strategic choices? and (c) Does the structure of questions explain strategic choices? Results of the content analysis suggest that format and question content affect candidates' strategic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…In comparative analyses of presidential debate content , Carlin, Howard, Stanfield, and Reynolds (1991) revealed considerable clash between presidential candidates. In later analyses, Carlin, Morris, and Smith (2001) found that the extent of clash is related to the debate format (e.g., town hall vs. mediator facilitator formats). In addition, Benoit and Harthcock (1999) and Benoit, Pier, Brazeal, McHale, Klyukovski, and Airne (2002) noted three functions of candidate verbal utterances in both primary and general-election presidential debates: Candidates acclaim themselves, attack their opponent(s), and defend themselves.…”
Section: Presidential Debate Contentmentioning
confidence: 85%
See 2 more Smart Citations
“…In comparative analyses of presidential debate content , Carlin, Howard, Stanfield, and Reynolds (1991) revealed considerable clash between presidential candidates. In later analyses, Carlin, Morris, and Smith (2001) found that the extent of clash is related to the debate format (e.g., town hall vs. mediator facilitator formats). In addition, Benoit and Harthcock (1999) and Benoit, Pier, Brazeal, McHale, Klyukovski, and Airne (2002) noted three functions of candidate verbal utterances in both primary and general-election presidential debates: Candidates acclaim themselves, attack their opponent(s), and defend themselves.…”
Section: Presidential Debate Contentmentioning
confidence: 85%
“…This study builds on that body of literature, and examines verbal content in ways previously unexplored in this body of research. Whereas scholars have enhanced understandings of the nature of discourse during debates, in terms of arguments and clash (Carlin, 1992;Carlin et al, 1991;Carlin et al, 2001) and have unearthed rhetorical moves debaters make (e.g., acclaims, attacks, and defenses; see Benoit & Harthcock, 1999;Benoit, McHale, Hansen, Pier, & McGuire, 2003;Benoit et al, 2002), this study examines the structure of language in debates and how debaters' language use positions them within a context of issues created by their participation. Like Benoit (2003Benoit ( , 2004, this study's interest is in how campaign messages may differentiate candidates and how that might be related to who wins and loses elections, albeit not the determining factor of electoral outcomes.…”
Section: Presidential Debate Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The press serves as the primary facilitator of the debate agenda. Scholars (Ben-Porath, 2007;Carlin, Morris, & Smith, 2001;Morello, 2005) have observed that moderators sometimes favor agendas that satisfy infotainmentdriven news values (e.g., soft news, campaign strategy, and character traits) over policy issues. An analysis of early presidential debates found that issues moderators asked about were unreflective of the issues salient to the public (Jackson-Beeck & Meadow, 1979).…”
Section: Lowering the Bar: Media Moderators In The New News Environmentmentioning
confidence: 99%
“…Scholars have found that the public debate agenda is less focused on conflict than the media's (Carlin et al, 2001;Kaid et al, 2000;Morello, 2005;Schroeder, 2008). Morello (2005) observed that public questions focus on plans and proposals, whereas press questions concern conflict and contradictions of the past.…”
Section: Lowering the Bar: Media Moderators In The New News Environmentmentioning
confidence: 99%